2019
DOI: 10.1177/2059513119896954
|View full text |Cite
|
Sign up to set email alerts
|

The use of a non-medicated dressing for superficial-partial thickness burns in children: a case series and review

Abstract: Background: Cutimed® Sorbact® is a dressing marketed as having antimicrobial properties and easy application without the threat of antibiotic resistance and difficult accessibility. There is little evidence on the clinical outcomes of the use of Cutimed® Sorbact® in adults and currently no evidence of use of Cutimed® Sorbact® on superficial-partial thickness burn injuries in children. Objective: To summarise the clinical outcome of burn wounds in children with superficial-partial thickness burns in which Cutim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…DACC wound dressing has also been used in the treatment of first, second and third degree burns in patients of pediatric age, reducing re-epithelialisation times with minimal psychological distress and no side effects in a group of ten patients. 58 In our experience, DACC wound dressing is extremely effective in the treatment of burns of the extremities, where it prevents the scar fusion of the digits, controls pain and reduces the appearance of interphalangeal keloids.…”
Section: The Benefits Of Dacc Technology Dressingsmentioning
confidence: 98%
See 1 more Smart Citation
“…DACC wound dressing has also been used in the treatment of first, second and third degree burns in patients of pediatric age, reducing re-epithelialisation times with minimal psychological distress and no side effects in a group of ten patients. 58 In our experience, DACC wound dressing is extremely effective in the treatment of burns of the extremities, where it prevents the scar fusion of the digits, controls pain and reduces the appearance of interphalangeal keloids.…”
Section: The Benefits Of Dacc Technology Dressingsmentioning
confidence: 98%
“…A small observational case series in 10 children (mean age = 2.49 years, range 11 months -8 years) with superficial-partial burns (TBSA range 4-14%, mean = 8%) showed that DACC wound dressing was effective at promoting wound progression in these burn wounds, with 50% of wounds healing within seven days and 100% of wounds healing within 21 days. 58 Few clinical studies have examined the effect of DACC wound dressings on the incidence of wound infection. Meberg and Schøyen 59 reported on umbilical cord care and prevention of infection in a large prospective randomised trial of 2441 infants who received either DACC wound dressing or daily cleansing of the wound with 0.5% chlorhexidine/70% ethanol.…”
Section: Pediatric Wounds and Wound Dressingsmentioning
confidence: 99%
“…9 The use of traditional medicines as a safe, affordable and simpleto-use approach with limited side effects these days is becoming reconsidered in different countries. 10 Sea buckthorn is of evergreen plants grown mostly in a moderate climate and at high altitudes in many parts of the world, including Europe and Asia. 11 Sea buckthorn has been applied as a topical medicine for wound repairing in some traditional medicine methods.…”
mentioning
confidence: 99%
“…(Deutzmann et al, 1990;Taniguchi et al, 2009) Thus, although LM511-E8 is substantially smaller (~150 kDa) than the full-length protein (~800 kDa), it serves as a functionally minimal form of LM511 and retains the key characteristics of the full-length protein including integrinbinding and dystroglycan binding sites that support adhesion and migration. (Doi et al, 2002;Kumai et al, 2019;T. Miyazaki et al, 2012;Y.…”
Section: Figure 20 Focal Adhesion Formationmentioning
confidence: 99%